Innovative Approaches to Enhancing the Biomedical Properties of Liposomes - Ioana Lavinia Dejeu; Laura Grațiela Vicaș; Eleonora Marian; Mariana Ganea; Olimpia Daniela Frenț; Paula Bianca Maghiar; Flaviu Ionut Bodea; George Emanuiel Dejeu (Pharmaceutics)
Liposomes represent a promising class of drug delivery systems that enhance the therapeutic efficacy and safety of various pharmaceutical agents. Also, they offer numerous advantages compared to traditional drug delivery methods, including targeted delivery to specific sites, controlled release, and fewer side effects. This review meticulously examines the methodologies employed in the preparation and characterization of liposomal formulations. With the rising incidence of adverse drug reactions, there is a pressing need for innovative delivery strategies that prioritize selectivity, specificity, and safety. Nanomedicine promises to revolutionize diagnostics and treatments, addressing current limitations and improving disease management, including cancer, which remains a major global health challenge. This paper aims to conduct a comprehensive study on the interest of biomedical research regarding nanotechnology and its implications for further applications.